Optical and Elastic Properties of Diamond-like Carbon with Metallic Inclusions: a Theoretical Study - Tritsaris, Georgios A.; Kelires, Pantelis C.; Mathioudakis, Christos (My University, 2012)
A tough material commonly used in coatings is diamond-like carbon (DLC), that is, amorphous carbon with content in four-fold coordinated C higher than ∼70, and its composites with metal inclusions. This study aims to offer useful guidelines for the design and development of metal-containing DLC coatings for solar collectors, where the efficiency of the collector depends critically on the performance of the absorber coating. We use first-principles calculations based on density functional theory to study the structural, electronic, optical, and elastic properties of DLC and its composites with Ag and Cu inclusions at 1.5 and 3.0 atomic concentration, to evaluate their suitability for solar thermal energy harvesting. We find that with increasing metal concentration optical absorption is significantly enhanced while at the same time, the composite retains good mechanical strength: DLC with 70-80 content in four-fold coordinated C and small metal concentrations (3 at. ) will show high absorption in the visible (absorption coefficients higher than 10 5 cm-1) and good mechanical strength (bulk and Youngs modulus higher than 300 and 500 GPa, respectively).
Keywords: Coatings; Elasticity; Metals; Solar energy; Diamond deposits